1993
DOI: 10.1128/mcb.13.3.1666
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of transcriptional activation functions of the NF-kappa B p50 and p65 subunits in mammalian cells and Saccharomyces cerevisiae.

Abstract: The NF-KB transcription factor complex is composed of a 50-kDa (p50) and a 65-kDa (p65) subunit. Both subunits bind to similar DNA motifs and elicit transcriptional activation as either homo-or heterodimers. By using chimeric proteins that contain the DNA binding domain of the yeast transcriptional activator GALA and subdomains of p65, three distinct transcriptional activation domains were identified. One domain was localized to a region of 42 amino acids containing a potential leucine zipper structure, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 65 publications
(125 reference statements)
2
49
0
2
Order By: Relevance
“…Both family members contain at least one transcription activation domain which makes them responsible for gene induction [25]. Since these observations were obtained in the human species, the need exists to demonstrate the presence of both proteins in their bovine counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Both family members contain at least one transcription activation domain which makes them responsible for gene induction [25]. Since these observations were obtained in the human species, the need exists to demonstrate the presence of both proteins in their bovine counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, these workers suggested that a pattern of aromatic and large hydrophobic amino acids plays a critical role in mediating activation of transcription by VP16. In this study, we sought to test the generality of this observation by functional dissection of the highly potent transcription activation domain of the RelA(p65) subunit of the inducible cellular transcription factor NF-KB (1,40). This 135-amino-acid (aa) activation domain has previously been shown to contain at least three discrete activation subdomains and has characteristics of both an acidic and a proline-rich transcriptional activator (31,41). Here, we provide evidence suggesting that this domain likely contains at least three discrete acidic activation modules (AAMs) centered on three phenylalanine residues.…”
mentioning
confidence: 99%
“…Immuno¯uorescence analysis was performed using an antibody speci®c for the C-terminal region of RelA domain, which has been localized between amino acids 416 and 550 Moore et al, 1993;Blair et al, 1994). This domain is highly conserved throughout species; 86% and 37% amino acids of human p65 protein are identical to those of mouse and chicken RelA respectively (Nolan et al, 1991;Ikeda et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This domain is highly conserved throughout species; 86% and 37% amino acids of human p65 protein are identical to those of mouse and chicken RelA respectively (Nolan et al, 1991;Ikeda et al, 1993). Three independent and cooperating acidic activating modules (AAMs) have been identi®ed in this region (Moore et al, 1993;Blair et al, 1994). In particular, each module consists of bulky, mainly acidic hydrophobic amino acids, surrounding a phenylalanine residue; mutation of phenylalanines 444, 473 and 541 reduces or abrogates the transcriptional activity of RelA (Blair et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation